Hubungan Antara Umur Dan Lama Paparan Dengan Gangguan Fungsi Paru Pada Pekerja Terpapar Debu Kapas Di Bagian Winding Pt.Bintang Makmur Sentosa Tekstil Industri Sragen - SARI, KARTIKA RATNA (2016)
Cotton dust, including organic dust containing carbon that are as fibrosis of the lungs. The research objective for know the relationship between age and length of exposure with lung function capacity in workers exposed to cotton dust at the Winding PT. Bintang Makmur Sentosa Textile Industry Sragen. This type of research is analytic survey with cross sectional approach and the sample size of 32 people. Sample collection technique used purposive. Data analysis was performed using univariate, bivariate with the Shapiro-Wilk test and if the data is normally distributed then followed by a test of Pearson Product Moment Correlation. The results of this study showed the average dust concentration of cotton at 10 points is 7,975 mg / M3. Lung Function Test results Capacity for FEV1% on average 98.20% and FVC% on average 66.39%. The results of Pearson Product Moment Correlation test shows its age with FEV1% and FVC% of all significant with p-value 0.047% FEV1 <0.05 value r p-value 0.562 and 0.041% FVC <0.05 value r 0.482. While long exposure with FEV1% and FVC% of all significant with p-value 0.037% FEV1> r value of 0.05 and a p-value 0.688% 0.039 FVC <0.05 value r 0.652. It can be concluded that the age and duration of exposure had a significant relationship with lung function capacity